PENGARUH DEBT RATIO, TOTAL ASSET TURNOVER, DAN CURRENT RATIO TERHADAP RETURN SAHAM SEKTOR INFRASTRUKTUR TAHUN 2015-2021 - Fauzan Aryaputra; Kaluge, David (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to examine the effect of Debt ratio, Total asset turnover, and Current ratio on the company’s stock return. This study uses a sample of 15 companies from infrastructure sector from 2015-2021. The analysis technique used is in the form of multiple linear analysis using Debt ratio, Total asset turnover, and Current ratio as the independent variable and stock return as a dependent variable and analyzed with the application of E-views 12. The results show that Total asset turnover, and Current ratio influences the company's stock return. In further analysis, debt ratio do not affect the company's stock returns. Companies must maintain it’s leverage and liquidity to increase company’s performance financially This will affect the credibility of the company so that it can affect investors' perceptions of companies in the infrastructure sector.